If f(x) = 5 – x and g(x) = 3x + 7, simplify f(2x) + g(x – 1)

There are two stages to this problem: substituting x into the original equation and then expanding out the answer and simplify it. So, with the first stage, we replace every old 'x' with the new form in the brackets (i.e. for f(2x), the equation would become 5 - (2x) rather than 5 - x ). So:f(2x) = 5 - 2xg(x-1) = 3(x-1)+7
Then, you expand it out:f(2x) + g(x-1) = 5 - 2x + 3(x-1) + 75 - 2x + 3x - 3 + 7
Then collect like terms and simplify:- 2x + 3x + 5 - 3 + 7 x + 9
Therefore, the answer is x + 9

Answered by Emma C. Maths tutor

10949 Views

See similar Maths GCSE tutors
Cookie Preferences